The Effect Additives in Avtur for Increasing Electrical Conductivity with Statistical Quality Control Method - Oksil Venriza; Doni Putra Pratama (Universitas Dharma Wacana, 2022)
The distributing processing Avtur to customers with a good quality according to standards. The parameter quality of avtur such as density, electrical conductivity, colour, and water content. One of them the electrical conductivity was investigated daily operation of distribution avtur if a demand avtur needed for flight operation, because that standard specifications of electrical conductivity Avtur must be good stability. The electrical conductivity value avtur less than standard operation cause static electrical to appear and became causes a fire. For this reason, a strategy is needed to increasing quality of Avtur by using the Statistical Quality Control (SQC) method. The result of analysis of level decline electrical conductivity to avtur using the SQC method has 6.6335 pS/m per day. Therefore, a strategy is needed to increase the electrical conductivity value, and optimalization for adding additive X. However, a facility to adding additives X has not implementation for receiving processing avtur, than suggestion to add additive injection facility. After implementation of additive injection facility, the value of electrical conductivity requires the addition of additives as become to 211.442 cc comparization before add additive is 103,595 cc.